Self-governance of ethical leadership in Malaysian public sector :conceptual content analysis and pattern matching analysis - Mohamed, Norazamina; Marha Yaakub, Najihah; Ahmad, Suraya; Abdullah, Azizah (International Journal of Engineering and Technology, 2018)
Public sector agencies are the main backbones of the Malaysian government in providing efficient public services. In 60 years of Malaysian Independency, this sector has continually assisted Malaysia to grow progressively. According to Corruption Index, Malaysia remains a score of less than 50% which indicates corruption is still occurring in this country. One of the reasons for the wrongdoings is due to the absence of ethical leadership. Thus, the objectives of this paper are to explore the attributes of ethical leadership in Malaysian public sector and to pattern match between ethical leadership with human behavior and social theories. This study employed a qualitative research by focusing on first-order concepts (through interviews) and second-order concepts (using theories to explain the facts). The data were analyzed by performing the conceptual content analysis (NVivo11) which then performed the pattern matching data analysis by matching the findings with the human behavior and social theories (under second-order concepts). This study revealed eight (8) attributes of ethical leadership which were role model, attachment, ethical support, knowledgeable, disciplined, leadersâ€™ spirituality encouragement, virtue values and shared values. These attributes are very much related to the social learning theory/idealism philosophy/social transactions, attachment theory, virtue ethics theory, divine command theory, social bonding theory and AlGhazali Theory of Virtue. It is suggested that the attributes of ethical leadership should become the ethical identity and ethical direction of Malaysian Public Sector. Instilling ethical leadership will enhance the public trust as well as the international community trust towards public sector.Â Â